Prevalence of Gingivitis in Patients Undergoing Orthodontic Treatment Between Age Group Of 25-35 Years - A Retrospective Study - M, ASHFAQ AHMED; RAMAMURTHY, JAIGANESH; DINESH, S.P.SARAVANA (The journal of contemporary issues in business and government, 2021)
Malocclusion is the misalignment or incorrect relation between the teeth and the dental arches. It is one of the leading causes of progression towards poor oral hygiene. Fixed orthodontic treatment is preferred and the most common method for treating malocclusions. Fixed appliances such as brackets, bands, or fixed retention may complicate optimal oral hygiene, and this may result in accumulation of dental plaque and gingival inflammation. S. mutans is the most common bacteria seen in the gingival sulcus. Prevention can be done by adequate oral prophylaxis prior to the commencement of orthodontic treatment. Thus the aim of the study is to assess the prevalence of gingivitis in patients undergoing orthodontic treatment between age 25-35 years. Evaluation of patients reported to saveetha dental college for the purpose of undergoing orthodontic treatment were chosen. 463 Patients data records were collected and descriptive statistics was done using SPSS software version 23 and the results obtained were tabulated and statistically analysed using the chi square test. It is observed that patients who developed gingivitis during orthodontic treatment belong to the age group of 25-30 years (56.16%) and 30- 35 years (16.41%) and the results are statistically significant (p<0.05). Males (39.96%) were commonly affected with gingivitis when compared to females (32.61). Thus it is important to understand the importance of the maintenance of oral hygiene during orthodontic treatment and patients should be made aware about the consequences of the ignorance to adopt adequate oral hygiene measures.